Оценка значимости технологических процессов на текстильных предприятиях - Нуриев, Магеммадали Нуреддин оглы; Мусаева, Тарана Тахир кызы (НТУ "ХПИ", 2015)
Изложена задача оценки значимости технологических процессов на текстильных предприятиях. Предложенная методика, которая позволяет определить их влияния на результативность структурных подразделений. Значимость процессов рассчитана с применением методологии функционально-стоимостного анализа. В качестве примера выбран оптимальный вариант совершенствования процессов материально-технического снабжения и подтверждена его эффективность.

The problem of estimation of the importance of processes of textile enterprises. This assessment allows the impact of the structural divisions of the enterprise processes on the effectiveness of management. The calculation of the importance of processes using the methodology of value analysis. On the example of the logistics process, the best option is selected and confirmed its effectiveness. Assess the relevance of technological processes of structural subdivisions, while ensuring the effectiveness of the quality management system. This assessment allows you to determine the degree of influence of processes of structural subdivisions of enterprises on the effectiveness of the QMS. In accordance with the methodology of functional-cost analysis of the significance of the processes of structural subdivisions based on the cost of quality.
Assess the significance of technological processes of textile enterprises
Keywords: функционально-стоимостной анализ; иерархические уровни; материально-техническое снабжение; оптимальный вариант; textile companies; value analysis; hierarchical levels